(untitled) (Contemporary Issues in Social Sciences and Management Practices, 2024)
Maritime sector is considered to be one of the most neglected sector of Pakistan. Contemporary world politics is now based on economy. History tells us those states that were fully aware of strengthening their maritime sector, they ruled the world. Competition over a sea lines of communications in Indian ocean region is increasing day by day.US tilt towards India became a driving force to strengthen collaboration between China and Pakistan. China Pakistan Economic Corridor is one of the significant example of strong ties between two states. China wants to penetrate in middle east along with central Asian states. Recent peace deal media by China with Iran and Kingdom of Saudi Arabia is its significant example. Development of Pakistani Gwadar port is one of the Chinese driving force to execute Chinese presence in the Indian ocean region. On the other hand, US wants to contain China via India. US is reluctant to reduce its presence in the region. 21st century belongs to trade and investment. This paper aims to highlight the geopolitical importance of trade related activities via sea lines of communications. Security of the sea routes along with its geopolitical significance in this security led architecture of the world is also discussed in the paper.